Implementation of multispecies ecological networks at the regional scale: analysis and multi-temporal assessment. (1st July 2021) - Modica, Giuseppe; Praticò, Salvatore; Laudari, Luigi; Ledda, Antonio; Di Fazio, Salvatore; De Montis, Andrea
Abstract: Today, major landscape changes affect ecological connectivity exerting adverse effects on ecosystems. Connectivity is a critical element of landscape structure and supports ecosystem functionality. Landscape connectivity can be efficiently increased in landscape ecology by building ecological networks (EN) through models mimicking the interaction between animal and vegetal species and their environment. ENs are important in sustainable landscape planning, where they need to be studied both by applying landscape metrics and by performing multi-temporal analyses. This paper presents theoretical and practical evidence of an analysis of a multispecies ecological network in Calabria (Italy) and its changes over three decades. Landscape connectivity was modeled basing on 66 focal faunal species' requirements. Human disturbance (HD) was defined and assessed according to distance from different disturbance sources. This allowed for the definition of overall habitat quality (oHQ). Landscape permeability to the animal movement was focused as the main concept to measure landscape fragmentation. Landscape graph theory was applied to perform a spatial comparison of the ENs robustness. Many binary and probabilistic indices and landscape morphological spatial pattern analysis (MSPA) were used in this perspective. We obtained a set of ecological networks, including nodes, patches (i.e., habitat patches), linkages, and corridors, all intertwined in one giant component. The multi-temporal analysis showed many indices' stationary values, while MSPA yielded an increase of habitat quality and habitat patches in core areas. This methodological approach allowed for assessing the regional EN's robustness in the time-span considered, thus providing a reliable tool for landscape planners and communities. Highlights: A design of multispecies ecological networks (EN) at a regional scale is proposed. The multi-temporal assessment is based on a set of spatial network indicators. Landscape connectivity was modeled based on the different species requirements. EN configuration evolved over time mantaining its potential for biodiversity conservation. EN components should be considered as structural invariants of planning tools.